MERUBAH PERILAKU MASYRAKAT RUSUN MARUNDA MELALUI PENDIDIKAN KETERAMPILAN - Connie Chairunnisa (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
Abstract:Emprower people in the middle complexity problem in Indonesia, needs of enormous energy very great, and needs collaboration traffic sector, like education sector, health sector, and sectors of the real, also include defence sucurity, and overseas. One of the weakness empowerment program in order poverty alleviation weak ability to entreprise in sociaty. Activities empowerment in Rusun Marunda north jakarta be conducted through eztention in three sphere ( cognitive, afective, and psikomotoric), in addition to be granted science, motivation, and intrepreneure also skill of making soap ekonomis, having excellence compared den other product . Empowerment through extension not the only just give information to society, but through the mother participants extensiont the domiciles in Rumah susun Marunda as much as 30 people, expected to may behaviour change towords that is expected to have skills can help family life. Keyword: Behavior, Rusun Marunda community, Skill.